Implikasi Keunggulan Bersaing Terhadap Kinerja Organisasi Pada Sektor Industri Manufaktur Kimia Di Provinsi Banten - Uli Wildan Nuryanto; Masyhudzulhak Djamil MZ; Achmad Hidayat Sutawidjaya; Ahmad Badawi Saluy (Kajian Akuntansi, 2020)
In current dynamic business environment, the competition is getting stiffer and performance organizational becomes issue, the caracteristics that occurred in the industrial revolution 4.0. This condition requires organizations to increase the performance to be sustain. Competence and knowledge management as internal resources that reffer to RBV are strengths hat are very important as predictors in improving performance. For this reason, the study has explored the indicators of each of the predictors and also test the relationships between latent variable that have been hypothesized. This research focus to the industrial chemical manufactur at Banten Province Indonesia which is become the province with the third largest number of chemical firms in Indonesia. Regarding to the central bureau statistics of Indonesia, the values of productivity and human resources capability from downstream chemical manufactur sector below the target. This research using SEM-PLS method to measure 97 respondents from the level supervisor and manajerial. The final results provide a positive and significant relationship between competence and knowledge management through competitive advantage and organizatioan performance. Competitive advantage also increasse the relationship between competence and knowledge management through the organizational performance. This result has implication for managerial levels to increase human resources performance so it can improve the firm competitive advantage.